Analysis the Role of Media Perspectives on General Communication and Islamic Communication - Junita Irawati (Budapest International Research and Critics University, 2020)
Research on general communication and Islamic perspective communication Public communication is an issue that is often discussed in human life today, because with communication can move the human condition. With communication, even a community can find out information. Likewise Islamic communication themes are found in the Qur'an. The terminology of communication in al-Qur'an includes, among others: Al-Ittiāşal, al-I’lam, al-Tabshīr, al-Da'wah, al-Bayan, al-Naba, al-Khabar, al-Qaul. This sentence is understood as the basic word of communication which is the basis for making that communication exist in the Qur'an. This research method uses a library research approach and content study. Using intrapersonal communication theory.